Impact of surgery and its complications in ulcerative colitis patients in clinical practice: A systematic literature review of real-world evidence in Europe. (2020) - Fradet, C.; Kern, J.; Atanasov, P.; Wirth, D.; Borsi, A.
Abstract: Background: Surgery plays an important role in the management of ulcerative colitis. Despite its curative intent, complications of the procedure are common and can have significant consequences to patients and care providers. We reviewed outcomes and rates of colectomy and its complications in ulcerative colitis (UC) patients in clinical practice. Materials and methods: MEDLINE, MEDLINE In-Process, Embase and Cochrane databases were searched for observational studies (January 2006–May 2017) reporting outcomes of surgery in moderate to severe UC in European countries. Studies were included if they reported colectomy rates, complications rate, predictors of colectomy and change in diagnosis in ulcerative colitis at the time of surgery. Results: 114 publications reporting either colectomy rates, postoperative complications or predictors of colectomy were identified. The overall rate of surgery from treatment initiation was reported in 20 articles and varied from 6% to 56% (follow-up time from 0.5 to 9 years). Early complications (≤30 days post-operatively) occurred in 0%–53% of patients undergoing surgery and late complications (>30 days post-operatively) occurred in 3.20%–58%. The common complications reported after colectomy (proctocolectomy or ileal pouch-anal anastomosis) were bowel obstruction, infectious complications and pouch-related complications (pouchitis, pouch failure). Three factors were found to be significant predictors of colectomy: a severe disease at baseline, being resistant to steroids and being frequently hospitalised. Conclusion: Colectomy rates vary widely among ulcerative colitis patients depending on type of patients (moderate, severe, refractory) and to patient's previous medical therapies. Surgery is still associated with a range of short and long term complications which might represent a source of burden in terms of cost and quality of life. Highlights: Colectomy rates vary widely among ulcerative colitis patients depending on type of patients (moderate, severe, refractory). Colectomy rates vary widely among ulcerative colitis patients depending to patient's previous medical therapies. Surgery is still associated with complications such as bowel obstruction, infectious and pouch-related complications. A severe disease at baseline and resistance to steroids were found to be significant predictors of colectomy. Postoperative mortality rates in ulcerative colitis patients remain low.